Commitment and Participation Affecting The Effectiveness of Personnel Performance at Kanchanaburi Highway Construction Center Department of Highway. - Bunyong, Dawluk; Kitiyanan, Sanchai; Bamrungkhet, Rattima; Pitakchuchok, Muttaneeya (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
The purposes of this research were to study commitment of personnel performance to study participation of personnel performance to study effectiveness of personnel performance and to study commitment and participation affecting to effectiveness of personnel performance at Kanchanaburi highway construction center department of highway. The population in the research includes personnel filled, personnel receiving salary and personnel receiving included welfare included 190 and simple random sampling for personnel performance at Kanchanaburi highway construction center department of highway. A constructed 5-level rating scale index of Item objective congruence was used as tool to collect data. The statistics used for data analysis were percentage, mean, standard deviation, and multiple regressions. The research findings revealed that: 1. Commitment of personnel performance at Kanchanaburi highway construction center department of highway sort by mean have a most level of normative commitment, most level of affective commitment and very level of continuance commitment. 2. Participation of personnel performance at Kanchanaburi highway construction center department of highway sort by mean have a very level of participation in implementation, very level of participation in benefits, moderate level of participation in evaluation, and moderate level of participation in decision making. 3. Effectiveness of personnel performance at Kanchanaburi highway construction center department of highway sort by mean have a most level of effectiveness in Latency, most level of effectiveness in Integration, most level of effectiveness in Integration and very level of effectiveness in goal attainment. 4. Commitment and Participation affecting the Effectiveness of personnel performance at Kanchanaburi Highway Construction center Department of highway, of 17.40 %, at written in the multiple regression analysis equation: Effectiveness of personnel performance = 3.82**+0.14 Commitment* + 0.26 Participation** Article history: Received 19 November 2019 Revised 12 December 2019 Accepted 15 December 2019 SIMILARITY INDEX= 1.05 %